Assessment and vision for the Philippine coconut industry - Escueta, E.U. (1998)
Assesses the industry and focuses on the vision. Looks at the legislative framework and highlights the 'Maunlad no Niyugan Tugon sa Kahirapan' programme and the model coconut farm. Notes the role of the Philippine Coconut Authority.